IMPLEMENTATION OF THE BEPS CONTROL PLAN IN UKRAINE: CURRENT STATUS AND DEVELOPMENT PROSPECTS - Nazarova, Halyna (European Science, 2023)
The monograph is devoted to the study of the historical retrospective and the current state of functioning of the BEPS measures, taking into account the peculiarities of their implementation in Ukraine. The author examines in detail the peculiarities of a